State of the Simulation of Mesoscale Winds in the Mediterranean and Opportunities for Improvements - Anika Obermann-Hellhund (Atmosphere, 2022)
The Mediterranean region is a densely populated and economically relevant area with complex orography including mountain ranges, islands, and straits. In combination with pressure gradients, this creates many mesoscale wind systems that cause, e.g., wind gusts and wildfire risk in the Mediterranean. This article reviews the recent state of the science of several mesoscale winds in the Mediterranean and associated processes. Previous work, including case studies on several time ranges and resolutions, as well as studies on these winds under future climate conditions, is discussed. Simulations with grid spacings of 25 to 50 km can reproduce winds driven by large-scale pressure patterns such as Mistral, Tramontane, and Etesians. However, these simulations struggle with the correct representation of winds channeled in straits and mountain gaps and around islands. Grid spacings of 1–3 km are certainly necessary to resolve these small-scale features. The smaller grid spacings are widely used in case studies, but not yet in simulations over large areas and long periods, which also could help to understand the interaction between small-scale phenomena in separate locations. Furthermore, by far not all Mediterranean straits, islands, and mountain gaps were studied in-depth and many interesting Mediterranean small-scale winds still need to be studied.